Output uncertainty mitigation in competitive markets - Bingbing Li; Yan Long (Bielefeld University, Center for Mathematical Economics (IMW), 2024)
Output uncertainty is a major concern for industries prone to exogenous, persistent and large fluctuations in output, such as agriculture, wind and solar power generation, while technology adoption aimed at mitigating output uncertainty can improve social welfare. This paper constructs a competitive market model with random output fluctuations to examine the scale of technology adoption at the long-term equilibrium and its comparison with the social optimum. We show that the First Welfare Theorem no longer holds in general, and depending on the characteristics of the demand function, the scale of technology adoption in the competitive market may be greater or less than the socially optimal scale.
urn:nbn:de:0070-pub-29942743
Keywords: D50; D61; D62; 330; technology adoption; uncertainty mitigation; long-termequilibrium; non-optimal scale